Dispersion mechanism and characterization of wood pulp-based wetlaid/spunlace materials. (November 2021) - Zhang, Yinjiang; Gu, Jiahua; Zhuo, Wenting; Zhao, Defang; Zou, Zhuanyong; Lu, Yongqing; Zhu, Lifeng
Wood pulp-based wetlaid/spunlace (wetlace) materials had an in-use dry or wet strength, but relatively quickly breakdown in municipal sanitization systems without block, such as sewer or septic systems. In order to further study the mechanism and characterization of material dispersion process, the relationship between dispersion time and sample residual rate or dispersion rate was analyzed on the basis of previous research methods. Meanwhile, the crowding factor was introduced for evaluation and the material dispersion mechanism was comprehensively expounded. The dispersion properties of wood pulp-based wetlace materials with different Danufil length-to-diameter (L/D) ratios and contents could be clearly distinguished at the stirring rate of 220 rpm. Meanwhile, the crowding factor was between 14 and 60 when wetlace materials reached dispersion balance, and the increase in crowding factor of wood pulp/Danufil-water dispersion system resulted in increasing the required dispersion time. Overall, the dispersion process could be divided into four stages: stable state of relative dispersion rate (low level), rapid ascent phase, fast descent stage, and constant region again (high level).